Similarities and Differences Between Youth Who Engaged in Intrafamilial and Extrafamilial Sexually Abusive Behavior: An Exploratory Study. (January 2021) - van Vugt, Eveline; Garofalo, Carlo
This study examined differences between youth who engaged in intrafamilial (ISAB) and extrafamilial sexually abusive behavior (ESAB) on various characteristics covering the sociodemographic, offense-related, psychological, and environmental domains. A total of 85 Dutch male youth participated in this study. Information was obtained through self-report questionnaires and systematic screening of the case files. Youth who engaged in ISAB, compared with ESAB, came from larger families, were enrolled in higher levels of secondary education and started sexual offending at a younger age. Youth who engaged in ESAB were more frequently diagnosed with attention-deficit hyperactivity disorder (ADHD) and intellectual disabilities (ID) and primarily received longer treatment in the context of residential care. The findings are discussed in connection to the literature on (adult) sexual offending. The risk factors and criminogenic needs that distinguish youth who engaged in ISAB and ESAB appear different from those found in adult populations.